Pressure-sensitive adhesive sheet, optical laminate, and image display device

The adhesive sheet with a specified creep amount and elasticity rate addresses the peeling issue in image display devices, ensuring stability in high-temperature environments by preventing component separation.

JP2025016392AActive Publication Date: 2025-01-31NITTO DENKO CORP
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2024166259
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-31
Estimated Expiration
2043-07-21

AI Technical Summary

Technical Problem

Conventional adhesive sheets used in image display devices tend to peel off between components in high-temperature environments, particularly when the optical film contains a single-axis extension film or the adhesive sheet thickness is 50 μm or less.

Method used

An adhesive sheet with a creep amount of 10 μm or more and an elasticity rate of 1.0 MPa or more on its surface, measured using an atomic force microscope, is developed to prevent peeling between components in high-temperature environments.

Benefits of technology

The adhesive sheet effectively suppresses peeling between members of the image display device, preventing air intrusion and maintaining device functionality in high-temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016392000001_ABST
    Figure 2025016392000001_ABST
Patent Text Reader

Abstract

To provide a pressure-sensitive adhesive sheet suitable for inhibiting delamination between members of an image display device in high-temperature environments.SOLUTION: A pressure-sensitive adhesive sheet 1 has a first surface 1a and a second surface 1b, which are opposite to each other. The pressure-sensitive adhesive sheet 1 has a creep amount, as obtained by the following test, of 10 μm or more, and the first surface 1a has an elastic modulus G1, as measured with an atomic force microscope, of 1.0 MPa or more. The test is such that: A 500-gf load 54 is applied vertically downward to the pressure-sensitive adhesive sheet 1 adhering to a stainless-steel test plate 53 such that the bonding area is 10 mm in length times 10 mm in width, while the test plate 53 is kept fixed. After 3600 seconds from the start of the application of the load 54, the creep amount (dislocation amount) of the pressure-sensitive adhesive sheet 1 relative to the test plate 53 is measured.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet, an optical laminate, and an image display device. [Background technology]

[0002] Various image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices, generally include an optical laminate including an optical film such as a polarizing film and an adhesive sheet. An adhesive sheet is usually used for bonding between the optical films included in the optical laminate and for bonding between the optical laminate and an image display panel. A typical adhesive sheet is a sheet obtained by curing a monomer group including an acrylic monomer, a silicone monomer, etc. through polymerization and crosslinking. Patent Document 1 discloses an example of an adhesive sheet. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 3052972 Summary of the Invention [Problem to be solved by the invention]

[0004] In conventional image display devices, peeling tends to occur between members such as between the optical laminate and the image display panel, or between the adhesive sheet and the optical film, under high temperature conditions. According to the study by the present inventors, the problem of peeling between members tends to occur more significantly when an adhesive sheet produced by a method of curing an adhesive composition by irradiating it with light (photocuring method) is used. This problem can also occur when the optical film contains a uniaxially stretched film such as a polarizer, or when the thickness of the adhesive sheet is 50 μm or less (particularly 30 μm or less).

[0005] In view of the above, an object of the present invention is to provide a pressure-sensitive adhesive sheet that is suitable for preventing peeling between components of an image display device in a high-temperature environment. [Means for solving the problem]

[0006] As a result of intensive research, the present inventors have found that the creep amount, which is an index of the susceptibility of a pressure-sensitive adhesive sheet to distortion due to stress, and the surface elastic modulus affect peeling between members in a high-temperature environment. Based on the above findings, the present inventors have further researched and completed the present invention.

[0007] The present invention relates to A pressure-sensitive adhesive sheet having a first surface and a second surface opposed to each other, The creep amount determined by the following test is 10 μm or more, The pressure-sensitive adhesive sheet has an elastic modulus of the first surface of 1.0 MPa or more as measured using an atomic force microscope. Test: The adhesive sheet is attached to a stainless steel test plate at a joint surface of 10 mm long x 10 mm wide, and a load of 500 gf is applied vertically downward with the test plate fixed in place. The creep amount (displacement amount) of the adhesive sheet relative to the test plate is measured 3600 seconds after the load is applied.

[0008] Further, the present invention relates to The above adhesive sheet, An optical film including at least one selected from the group consisting of a polarizing film and a retardation film; The present invention provides an optical laminate comprising:

[0009] Further, the present invention relates to There is provided an image display device including the above optical laminate. Effect of the Invention

[0010] According to the present invention, it is possible to provide a pressure-sensitive adhesive sheet suitable for preventing peeling between components of an image display device in a high-temperature environment. [Brief description of the drawings]

[0011] [Figure 1] 1 is a cross-sectional view illustrating a schematic example of a pressure-sensitive adhesive sheet of the present invention. [Figure 2A] FIG. 2 is a schematic diagram for explaining a method for measuring the amount of creep for a pressure-sensitive adhesive sheet. [Figure 2B] FIG. 2 is a schematic diagram for explaining a method for measuring the amount of creep for a pressure-sensitive adhesive sheet. [Figure 3A] FIG. 4 is a diagram showing an example of an atomic force microscope image of a first surface of the adhesive sheet. [Figure 3B] FIG. 1 is a diagram showing an example of a histogram of elastic modulus measured by an atomic force microscope. [Figure 4] FIG. 2 is a diagram showing an example of an atomic force microscope image of a cross section of a pressure-sensitive adhesive sheet. [Figure 5A] 1A to 1C are schematic diagrams illustrating an example of a method for producing a pressure-sensitive adhesive sheet of the present invention. [Figure 5B] 1A to 1C are schematic diagrams illustrating an example of a method for producing a pressure-sensitive adhesive sheet of the present invention. [Figure 5C] 1A to 1C are schematic diagrams illustrating an example of a method for producing a pressure-sensitive adhesive sheet of the present invention. [Figure 5D] 1A to 1C are schematic diagrams illustrating an example of a method for producing a pressure-sensitive adhesive sheet of the present invention. [Figure 5E] 1A to 1C are schematic diagrams illustrating an example of a method for producing a pressure-sensitive adhesive sheet of the present invention. [Figure 6] FIG. 1 is a cross-sectional view illustrating an example of an optical laminate of the present invention. [Figure 7] FIG. 1 is a cross-sectional view illustrating an example of an optical laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The pressure-sensitive adhesive sheet according to the first aspect of the present invention is A pressure-sensitive adhesive sheet having a first surface and a second surface opposed to each other, The creep amount determined by the following test is 10 μm or more, The first surface has a modulus of elasticity of 1.0 MPa or more as measured using an atomic force microscope. Test: The adhesive sheet is attached to a stainless steel test plate at a joint surface of 10 mm long x 10 mm wide, and a load of 500 gf is applied vertically downward with the test plate fixed in place. The creep amount (displacement amount) of the adhesive sheet relative to the test plate is measured 3600 seconds after the load is applied.

[0013] In a second aspect of the present invention, for example, the pressure-sensitive adhesive sheet according to the first aspect has a first layer and a second layer located on the first layer, and the first surface coincides with the surface of the second layer.

[0014] In a third aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to the second aspect, the second layer has a thickness of 1.0 μm or less.

[0015] In a fourth aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to any one of the first to third aspects, the creep amount is 300 μm or less.

[0016] In a fifth aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to any one of the first to fourth aspects, the elastic modulus of the first surface is 10.0 MPa or less.

[0017] In a sixth aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to any one of the first to fifth aspects, the elastic modulus of the second surface measured using an atomic force microscope is less than 1.0 MPa.

[0018] In a seventh aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to any one of the first to sixth aspects, the first surface is a surface that has been subjected to a surface modification treatment.

[0019] In an eighth aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to the seventh aspect, the surface modification treatment is a corona treatment.

[0020] In a ninth aspect of the present invention, for example, the pressure-sensitive adhesive sheet according to any one of the first to eighth aspects is formed from a pressure-sensitive adhesive composition containing a group of monomers and / or a polymer of the group of monomers.

[0021] In a tenth aspect of the present invention, for example in the pressure-sensitive adhesive sheet according to the ninth aspect, the monomer group includes a (meth)acrylic monomer.

[0022] In an eleventh aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to the ninth or tenth aspect, the pressure-sensitive adhesive composition is photocurable.

[0023] In a twelfth aspect of the present invention, for example, in the pressure-sensitive adhesive sheet according to any one of the ninth to eleventh aspects, the pressure-sensitive adhesive composition has a solvent content of 5 wt % or less.

[0024] In a thirteenth aspect of the present invention, for example, the pressure-sensitive adhesive sheet according to any one of the first to twelfth aspects has a thickness of 50 μm or less.

[0025] The optical laminate according to the fourteenth aspect of the present invention is A pressure-sensitive adhesive sheet according to any one of the first to thirteenth aspects; An optical film including at least one selected from the group consisting of a polarizing film and a retardation film; Equipped with.

[0026] In a fifteenth aspect of the present invention, for example, in the optical laminate according to the fourteenth aspect, the first surface of the pressure-sensitive adhesive sheet is in contact with the optical film.

[0027] In a sixteenth aspect of the present invention, for example, in the optical laminate according to the fourteenth or fifteenth aspect, the anchoring force between the pressure-sensitive adhesive sheet and the optical film is 10.0 N / 25 mm or more.

[0028] An image display device according to a seventeenth aspect of the present invention includes the optical laminate according to any one of the fourteenth to sixteenth aspects.

[0029] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified in any manner without departing from the gist of the present invention.

[0030] [Embodiment of the adhesive sheet] An example of the adhesive sheet of this embodiment is shown in Fig. 1. The adhesive sheet 1 in Fig. 1 has a first surface 1a and a second surface 1b facing each other. As an example, the adhesive sheet 1 is attached to an optical film via the first surface 1a, and the adhesive sheet 1 is attached to an image display panel via the second surface 1b.

[0031] The adhesive sheet 1 has a creep amount of 10 μm or more as determined by the following test, and further has an elastic modulus G1 of 1.0 MPa or more as measured by an atomic force microscope (AFM) of the first surface 1a. Test: A load of 500 gf is applied vertically downward to the adhesive sheet 1 attached to a stainless steel test plate with a joint surface of 10 mm length x 10 mm width, while the test plate is fixed. The creep amount (amount of displacement) of the adhesive sheet 1 relative to the test plate is measured 3600 seconds after the load is applied.

[0032] According to the adhesive sheet 1 of the present embodiment, peeling between components of an image display device in a high temperature environment can be suppressed due to the creep amount and elastic modulus G1. In particular, peeling between the optical laminate and the image display panel tends to be suppressed when the creep amount is 10 μm or more. Peeling between the adhesive sheet 1 and the optical film tends to be suppressed when the elastic modulus G1 of the first surface 1a is 1.0 MPa or more. Since the suppression of peeling between components of the image display device suppresses air intrusion and misalignment of the optical film, when the adhesive sheet 1 of the present embodiment is used, problems tend not to occur in the image display function of the image display device.

[0033] Specifically, the creep amount of the adhesive sheet 1 can be evaluated by the following method (see FIG. 2A and FIG. 2B). First, the adhesive sheet 1 is attached to the support film 51 so that the first surface 1a of the adhesive sheet 1 faces the support film 51 to prepare a laminate. This laminate is cut into a rectangular shape of 10 mm×50 mm to prepare a test piece 52. The support film 51 is arranged for the purpose of suppressing deformation of the portion of the adhesive sheet 1 to which the load is applied during the test, thereby enabling the creep amount to be measured more accurately. For the support film 51, for example, a resin film such as a polyethylene terephthalate (PET) film can be used. The support film 51 may be an optical film or a laminate including an optical film. The thickness of the support film 51 may be a thickness that does not deform itself under the load, and is, for example, 20 to 200 μm. Next, as shown in FIG. 2A and FIG. 2B, the test piece 52 is attached to the surface of a stainless steel test plate 53 by the adhesive sheet 1 at a joint surface of 10 mm long×10 mm wide. FIG. 2B is a cross section BB of FIG. 2A. The test piece 52 is attached to the test plate 53 so that no air bubbles are mixed between the test plate 53 and the adhesive sheet 1. After attachment, the test plate 53 and the adhesive sheet 1 are homogenized by placing the test plate 53 and the adhesive sheet 1 in an autoclave at 50° C. and 5 atm (absolute pressure) for 15 minutes. Next, the test plate 53 and the test piece 52 are held vertically with the test plate 53 facing upward and left in an atmosphere at 25° C. for at least 5 minutes, and then a weight of 500 g is fixed to the center of the lower end of the test piece 52 with the test plate 53 fixed, and a load 54 of 500 gf is applied vertically downward. The creep amount (displacement amount) of the adhesive sheet 1 relative to the test plate 53 at a time 3600 seconds after the load 54 is applied is measured as the fall amount of the weight. A laser displacement meter can be used to measure the fall amount of the weight. The load 54 is applied in an atmosphere at 25° C.

[0034] As described above, in this embodiment, the creep amount of the adhesive sheet 1 is 10 μm or more. The creep amount of the adhesive sheet 1 is preferably 15 μm or more, and may be 20 μm or more, 30 μm or more, 40 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, 80 μm or more, 90 μm or more, 100 μm or more, 110 μm or more, 120 μm or more, or even 130 μm or more. The larger the creep amount of the adhesive sheet 1, the more likely it is that peeling between members of the image display device, particularly between the optical laminate and the image display panel, will be suppressed in a high-temperature environment. However, if the creep amount of the adhesive sheet 1 is excessively large, tears (glue tears) will tend to occur inside the adhesive sheet 1 in a high-temperature environment. According to the study by the present inventors, tearing of the adhesive sheet 1 in a high-temperature environment is particularly likely to occur in the adhesive sheet 1 produced by a method of curing an adhesive composition by irradiating it with light (photocuring method). In order to prevent tearing of the adhesive sheet 1 in a high temperature environment, the upper limit of the creep amount of the adhesive sheet 1 may be, for example, 500 μm or less, 400 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, 180 μm or less, 160 μm or less, or even 150 μm or less.

[0035] Specifically, the elastic modulus G1 of the first surface 1a can be evaluated by the following method. First, the adhesive sheet 1 is cut into a size of about 0.8 cm length × 0.5 cm width to prepare a test piece. Next, the test piece is fixed to a sample stage using conductive double-sided tape. At this time, the test piece is placed so that the second surface 1b of the test piece faces the sample stage and the first surface 1a is exposed to the outside. The test piece is left to stand for at least one hour to stabilize.

[0036] Next, using an AFM, the number of measurement points was 20 μm in an area of ​​20 μm in length and 20 μm in width on the first surface 1a of the test piece. 8The elastic modulus is measured so that the value is (256). At this time, the interval between adjacent measurement points is adjusted to about 1 μm. The elastic modulus is measured, for example, over the entire area of ​​20 μm vertical × 20 μm horizontal on the first surface 1a of the test piece. The elastic modulus can be determined by the JKR two-point method using a load-displacement curve obtained by force curve measurement. As the AFM, a commercially available scanning probe microscope (for example, MFP-3D Standalone manufactured by ASYLUM RESEARCH) can be used. The details of the elastic modulus measurement conditions are as follows. Measurement conditions Measurement mode: Force mode Cantilever: Olympus OMCL-AC240TS (resonant frequency: 75 kHz, spring constant: 1.7 N / m, tip shape: Sphere (hemisphere) (radius 10 nm), Poisson's ratio: 0.5) Scanning range: 20μm vertical x 20μm horizontal Number of data to be imported: 16 x 16 (256) Push-in speed: 1.98μm / s Trigger point: 0.05V Measurement temperature: 25℃

[0037] By the above measurement, data on the elastic modulus can be obtained for each of a plurality of positions on the first surface 1a of the test piece. By mapping this data, an AFM image as shown in FIG. 3A can be obtained. In this AFM image, visual information of a color tone is given to each pixel based on the numerical value of the elastic modulus. The size of one pixel in the AFM image corresponds to the size of the tip of the cantilever. The number of pixels constituting the AFM image corresponds to the number of measurement points.

[0038] Next, a histogram of the elastic modulus with a class width of 0.02 MPa is created (FIG. 3B). In this histogram, the horizontal axis indicates the elastic modulus, and the vertical axis indicates the frequency (number of measurement points). The elastic modulus (mode) corresponding to the maximum frequency value M in the histogram is identified as the elastic modulus G1 of the first surface 1a.

[0039] In this embodiment, the number of peaks present in the histogram created by the above method is preferably one. As an example, one peak P is shown in FIG. 3B. The peak P is typically unimodal. However, the histogram may have multiple peaks or a multimodal peak.

[0040] As described above, in this embodiment, the elastic modulus G1 of the first surface 1a is 1.0 MPa or more. For example, when the first surface 1a of the pressure-sensitive adhesive sheet 1 is in contact with an optical film, the elastic modulus G1 of 1.0 MPa or more tends to adjust the anchoring force between the pressure-sensitive adhesive sheet 1 and the optical film to a sufficiently large value. The elastic modulus G1 is preferably 1.1 MPa or more, and may be 1.2 MPa or more, 1.3 MPa or more, 1.4 MPa or more, 1.5 MPa or more, 1.6 MPa or more, 1.7 MPa or more, 1.8 MPa or more, or even 1.9 MPa or more. The upper limit of the elastic modulus G1 is not particularly limited, and may be, for example, 10.0 MPa or less, 5.0 MPa or less, 3.0 MPa or less, or even 2.0 MPa or less.

[0041] The elastic modulus G2 of the second surface 1b measured using AFM is not particularly limited, but is preferably smaller than the elastic modulus G1. The elastic modulus G2 may be, for example, less than 1.0 MPa, 0.9 MPa or less, 0.8 MPa or less, or even 0.7 MPa or less. The lower limit of the elastic modulus G2 of the second surface 1b may be, for example, 0.1 MPa or more, 0.3 MPa or more, or even 0.5 MPa or more. However, in some cases, the elastic modulus G2 of the second surface 1b may be 1.0 MPa or more, and may be within the above-mentioned range for the elastic modulus G1. The elastic modulus G2 of the second surface 1b can be measured by the same method as the elastic modulus G1 of the first surface 1a.

[0042] The first surface 1a of the adhesive sheet 1 is, for example, a surface that has been subjected to a surface modification treatment. The first surface 1a that has been subjected to a surface modification treatment tends to have a high elastic modulus G1. On the other hand, it is preferable that the second surface 1b of the adhesive sheet 1 has not been subjected to a surface modification treatment. Examples of the surface modification treatment include a corona treatment, a plasma treatment, an excimer treatment, and a frame treatment. It is preferable that the first surface 1a has been subjected to a corona treatment as a surface modification treatment.

[0043] The surface modification treatment may be performed in an inert gas atmosphere. By performing the surface modification treatment in a state where the oxygen concentration is reduced by an inert gas, the risk of ignition of the remaining monomers can be reduced. Specifically, it is preferable to perform the surface modification treatment at an oxygen concentration of 8% by volume or less. More preferably, it is 6% by volume or less, and even more preferably, it is 3% by volume or less. If the oxygen concentration is too low, the introduction of functional groups into the surface of the pressure-sensitive adhesive sheet 1 by the surface modification treatment may be insufficient, so the oxygen concentration is preferably 0.01% by volume or more, more preferably 0.1% by volume or more, and particularly preferably 0.5% by volume or more. Specific examples of the inert gas include nitrogen and argon. The surface modification treatment may be performed under normal pressure (1 atm).

[0044] The condition of the surface modification treatment, which is a corona treatment, is expressed in terms of the discharge amount, for example, 1 W / m 2 min or more, 10W / m 2 · min or more, 20W / m 2 · min or more, 30W / m 2 · min or more, 40W / m 2 · min or more, 50W / m 2 min or higher, even 60W / m 2 ·min or more. However, when corona treatment is performed on the first surface 1a of the pressure-sensitive adhesive sheet 1, if the discharge amount is excessively large, the elastic modulus will become uneven within the first surface 1a, and the elastic modulus G1 determined by the above method may not increase sufficiently. From the viewpoint of adjusting the elastic modulus G1 of the first surface 1a to an appropriate value, the discharge amount is preferably 400 W / m 2 min or less, 350W / m 2 ·Min or less, 300W / m2 ·Min or less, 250W / m 2 ·Min or less, 200W / m 2 ·Min or less, 150W / m 2 ·Min or less, 100W / m 2 min or less, even 80W / m 2 · May be less than min.

[0045] As shown in FIG. 1, the adhesive sheet 1 preferably has a first layer 5 and a second layer 6 located on the first layer 5. The second layer 6 is typically in direct contact with the first layer 5. The second layer 6 may cover the entire surface of the first layer 5, or may cover the surface of the first layer 5 partially. As an example, the first surface 1a of the adhesive sheet 1 coincides with the surface 6a of the second layer 6, and the second surface 1b of the adhesive sheet 1 coincides with the surface 5a of the first layer 5. The second layer 6 is typically a layer having a higher elastic modulus and a smaller thickness than the first layer 5. Note that the adhesive sheet 1 does not need to have a laminated structure of the first layer 5 and the second layer 6, and may be a single layer film, as long as the creep amount and the elastic modulus G1 of the first surface 1a are adjusted to the above range.

[0046] As described below, the first layer 5 and the second layer 6 can be produced, for example, by subjecting a cured sheet formed from a pressure-sensitive adhesive composition to a surface modification treatment. In detail, the second layer 6 having a high elastic modulus is formed in the portion subjected to the surface modification treatment, and the first layer 5 is formed in the remaining portion. The first layer 5 and the second layer 6 produced in this manner have the same composition, and can be said to be formed from the same pressure-sensitive adhesive composition.

[0047] The thickness of the first layer 5 is, for example, 500 μm or less, and may be 250 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, or even 20 μm or less. The lower limit of the thickness of the first layer 5 is, for example, 2 μm or more, and may be 5 μm or more. The thickness of the first layer 5 can be calculated based on, for example, the thickness of the pressure-sensitive adhesive sheet 1 and the thickness of the second layer 6.

[0048] The thickness of the second layer 6 is, for example, 1.0 μm or less, and may be 0.8 μm or less, 0.5 μm or less, 0.4 μm or less, 0.3 μm or less, 0.2 μm or less, or even 0.1 μm or less. The lower limit of the thickness of the second layer 6 is not particularly limited, and is, for example, 0.001 μm or more. The thickness of the second layer 6 tends to be sufficiently smaller than that of the first layer 5.

[0049] The thickness of the second layer 6 can be measured, for example, by the following method. First, the adhesive sheet 1 is attached to a support film so that the first surface 1a of the adhesive sheet 1 faces the support film to prepare a laminate. An optical film or the like can be used as the support film. The prepared laminate is frozen, and then cut in the thickness direction by an ultramicrotome to obtain a test piece. This test piece is a slice with a thickness of about 200 nm, and the main surface (the surface with the largest area) coincides with the cross section of the laminate. Next, this test piece is fixed on a silicon wafer and left to stand overnight to stabilize.

[0050] Next, using an AFM, two measurement points were measured in an area of ​​1 μm long x 1 μm wide near the interface between the adhesive sheet 1 and the support film on the main surface of the test piece. 14 The elastic modulus is measured so that the measured value is (16384). At this time, the interval between adjacent measurement points is adjusted to about 8 nm. The elastic modulus is measured, for example, over the entire area of ​​1 μm vertical × 1 μm horizontal on the main surface of the test piece. The elastic modulus can be determined by the JKR two-point method using the load-displacement curve obtained by force curve measurement. As the AFM, a commercially available scanning probe microscope (for example, MFP-3D Standalone manufactured by ASYLUM RESEARCH) can be used. The details of the elastic modulus measurement conditions are as follows. Measurement conditions Measurement mode: Force mode Cantilever: Olympus OMCL-AC240TS (resonant frequency: 75 kHz, spring constant: 1.7 N / m, tip shape: Sphere (hemisphere) (radius 10 nm), Poisson's ratio: 0.5) Scanning range: 1μm vertical x 1μm horizontal Number of imported data: 128 x 128 (16384) Push-in speed: 1.98μm / s Trigger point: 0.05V Measurement temperature: 25℃

[0051] Through the above measurements, data on the elastic modulus can be obtained for multiple positions on the main surface of the test piece. By mapping this data, an AFM image like the one shown in Figure 4 can be obtained. In this AFM image, visual information is given to each pixel in a color tone based on the numerical value of the elastic modulus. The size of one pixel in the AFM image corresponds to the size of the tip of the cantilever. The number of pixels that make up the AFM image corresponds to the number of measurement points.

[0052] As shown in FIG. 4, from the AFM image, in the region where the adhesive sheet 1 exists, a region with a relatively low elastic modulus (first layer 5) and a region with a relatively high elastic modulus (second layer 6) can be confirmed. The region with a relatively high elastic modulus exists near the interface between the adhesive sheet 1 and the support film. Based on the obtained AFM image, the thickness of the second layer 6 can be identified. In detail, the distance between the first layer 5 and the support film in the AFM image is measured at any multiple points (e.g., five or more points), and the average of the obtained values ​​can be regarded as the thickness of the second layer 6.

[0053] The thickness of the pressure-sensitive adhesive sheet 1 is, for example, 500 μm or less, and may be 250 μm or less, 150 μm or less, 100 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, or even 20 μm or less. The lower limit of the thickness of the pressure-sensitive adhesive sheet 1 is, for example, 2 μm or more, and may be 5 μm or more.

[0054] (Adhesive composition) The adhesive sheet 1 is formed, for example, from an adhesive composition containing a group of monomers and / or a polymer of the monomer group. In detail, the adhesive sheet 1 can be produced by subjecting a cured sheet formed from the above-mentioned adhesive composition to a surface modification treatment. The adhesive composition is preferably a photocurable adhesive composition (photocurable composition) that is cured by irradiation with light. However, the adhesive composition may also be a thermosetting adhesive composition that is cured by heat.

[0055] Generally, adhesive sheets are manufactured by, for example, the following thermosetting method. First, a crosslinking agent or the like is added to a polymer produced by polymerizing a polymerizable monomer in an organic solvent to prepare an adhesive composition. This adhesive composition is applied to a substrate such as a release liner, and the organic solvent is removed by heating to form a sheet. If necessary, heat aging is performed to complete crosslinking, thereby manufacturing an adhesive sheet. In this manufacturing process, a large amount of fuel such as LNG needs to be burned in order to generate the thermal energy required for the thermal removal of the solvent and for heat aging. In addition, if the organic solvent removed by heating is directly released into the atmosphere, it may have a significant adverse effect on the surrounding environment. Therefore, the organic solvent is often burned in a deodorizing furnace or the like before being released. In this case, not only is additional fuel required for combustion in the deodorizing furnace, but the organic solvent itself is also converted into CO2 by combustion and released into the atmosphere, resulting in a manufacturing process with extremely large CO2 emissions.

[0056] In recent years, climate change caused by greenhouse gases has become an urgent issue, and governments around the world have set numerical targets to reduce CO2 emissions. For this reason, it is preferable to select a manufacturing process that does not use organic solvents and has low CO2 emissions when manufacturing adhesive sheets. Methods that use light to create adhesive sheets (photocuring methods) tend to reduce the amount of energy required to form adhesive sheets and the amount of CO2 emissions compared to thermal curing methods.

[0057] According to the study by the present inventors, in the past, when a pressure-sensitive adhesive sheet formed from a photocurable pressure-sensitive adhesive composition is used, peeling tends to occur more easily between the components of the image display device, especially between the pressure-sensitive adhesive sheet and the optical film, compared to when a pressure-sensitive adhesive sheet formed from a thermosetting pressure-sensitive adhesive composition is used. This tendency is presumably due to the fact that when a pressure-sensitive adhesive sheet formed from a thermosetting pressure-sensitive adhesive composition is bonded to an optical film, the curing of the pressure-sensitive adhesive sheet further progresses on the surface of the optical film, whereas in the case of a pressure-sensitive adhesive sheet formed from a photocurable pressure-sensitive adhesive composition, curing hardly progresses after bonding to the optical film. In this embodiment, by adjusting the creep amount and the elastic modulus G1 of the first surface 1a to the above range, peeling between the components of the image display device tends to be sufficiently suppressed even when the pressure-sensitive adhesive sheet 1 is formed from a photocurable pressure-sensitive adhesive composition.

[0058] As described above, the adhesive composition includes a monomer group and / or a polymer of the monomer group. The monomer group includes, for example, a (meth)acrylic monomer. The content of the (meth)acrylic component in the adhesive composition, i.e., the (meth)acrylic monomer and its polymer, may be 50% by weight or more, 60% by weight or more, 70% by weight or more, or even 80% by weight or more. In this case, an acrylic adhesive sheet 1 containing a (meth)acrylic polymer and its crosslinked product as the main components can be formed. However, the adhesive composition is not limited to the above examples. In this specification, (meth)acrylic means acrylic and methacrylic. (Meth)acrylate means acrylate and methacrylate.

[0059] An example of the (meth)acrylic monomer is a (meth)acrylic acid alkyl ester having an alkyl group having 1 to 20 carbon atoms on the side chain. The number of carbon atoms in the alkyl group may be 7 or less, 6 or less, 5 or less, or even 4 or less. The alkyl group may be linear or branched. Examples of the (meth)acrylic acid alkyl ester are methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and the like. acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, n-nonyl (meth)acrylate, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, n-dodecyl (meth)acrylate (lauryl (meth)acrylate), n-tridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate and octadecyl (meth)acrylate. The (meth)acrylic acid alkyl ester may be n-butyl (meth)acrylate.

[0060] In 100 parts by weight of the monomer group, the amount of the (meth)acrylic acid alkyl ester may be, for example, 40 parts by weight or more, 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 85 parts by weight or more, 90 parts by weight or more, or even 95 parts by weight or more. In calculating the amount of a specific monomer, the weight of the polymer is converted into the weight of each monomer before polymerization.

[0061] The monomer group may contain a carboxyl group-containing monomer. The carboxyl group-containing monomer may be a (meth)acrylic monomer, in other words, the (meth)acrylic monomer may contain a carboxyl group-containing monomer. Examples of the carboxyl group-containing monomer are (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, and crotonic acid. The amount of the carboxyl group-containing monomer in 100 parts by weight of the monomer group may be, for example, 10 parts by weight or less, 9 parts by weight or less, 8 parts by weight or less, 7 parts by weight or less, 6 parts by weight or less, 5 parts by weight or less, 4.8 parts by weight or less, 4 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or even 0.5 parts by weight or less. The lower limit of the amount is, for example, 0.1 parts by weight or more, and in some cases, may be 0.5 parts by weight or more. The monomer group may not include a carboxyl group-containing monomer.

[0062] The monomer group may contain a hydroxyl group-containing monomer. The hydroxyl group-containing monomer may be a (meth)acrylic monomer, in other words, the (meth)acrylic monomer may contain a hydroxyl group-containing monomer. The hydroxyl group-containing monomer may contribute to improving the cohesive strength of the adhesive sheet. Examples of the hydroxyl group-containing monomer are 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)-methyl acrylate. The hydroxyl group-containing monomer is preferably 2-hydroxyethyl (meth)acrylate or 4-hydroxybutyl (meth)acrylate. In 100 parts by weight of the monomer group, the amount of the hydroxyl group-containing monomer may be, for example, 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, 7.5 parts by weight or less, 5 parts by weight or less, 4 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or even 0.5 parts by weight or less. The lower limit of the amount may be, for example, 0.01 parts by weight or more, 0.03 parts by weight or more, or even 0.05 parts by weight or more. The monomer group may not contain a hydroxyl group-containing monomer.

[0063] The monomer group may include an ether group-containing monomer. The ether group-containing monomer may be a (meth)acrylic monomer, in other words, the (meth)acrylic monomer may include an ether group-containing monomer. The ether group-containing monomer can contribute to improving the anchoring force between the pressure-sensitive adhesive sheet 1 and the optical film.

[0064] The ether group-containing monomer is preferably an alkoxy group-containing monomer. Examples of the alkoxy group-containing monomer include an alkylene oxide adduct represented by the following chemical formula (A). R in formula (A) 1 R in formula (A) is a hydrogen atom or a methyl group. 2 R is an alkyl group. The alkyl group may be linear or branched. 2R is preferably a linear alkyl group. 2 Examples of n are a methyl group and an ethyl group. In formula (A), n is an integer of 1 to 30, preferably an integer of 1 to 12, and may be an integer of 1 to 5. [ka]

[0065] Examples of the alkylene oxide adduct shown in formula (A) are 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate and methoxypolyethylene glycol (meth)acrylate, preferably 2-methoxyethyl acrylate (MEA).

[0066] The ether group-containing monomer is not limited to the alkylene oxide adduct. The ether group-containing monomer may have a ring structure, and the ring structure may have an ether group. Examples of the ring structure having an ether group include a tetrahydrofuran ring and a dioxane ring. Examples of the ether group-containing monomer having a ring structure are cyclic trimethylolpropane formal (meth)acrylate and tetrahydrofurfuryl (meth)acrylate.

[0067] In 100 parts by weight of the monomer group, the amount of the ether group-containing monomer may be, for example, 1 part by weight or more, 5 parts by weight or more, 10 parts by weight or more, 20 parts by weight or more, 25 parts by weight or more, 30 parts by weight or more, 40 parts by weight or more, 50 parts by weight or more, 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, or even 90 parts by weight or more. The upper limit of the amount is, for example, 99 parts by weight or less, and in some cases, may be 50 parts by weight or less. The monomer group may not contain an ether group-containing monomer.

[0068] The monomer group may include a nitrogen atom-containing monomer. The nitrogen atom-containing monomer means a monomer having at least one nitrogen atom in the molecule (per molecule). In this specification, a monomer having a hydroxyl group and a nitrogen atom in the molecule is classified as a nitrogen atom-containing monomer. A monomer having a carboxyl group and a nitrogen atom in the molecule is classified as a carboxyl group-containing monomer.

[0069] The nitrogen atom-containing monomer is preferably N-vinyl cyclic amide, (meth)acrylamide, etc. The nitrogen atom-containing monomer may be used alone or in combination of two or more kinds.

[0070] The N-vinyl cyclic amide is preferably one represented by the following formula (B). [ka]

[0071] In formula (B), R 1 is a divalent organic group, preferably a divalent saturated or unsaturated hydrocarbon group, and more preferably a divalent saturated hydrocarbon group (e.g., an alkylene group having 3 to 5 carbon atoms). 1 are directly bonded via a single bond to form a ring structure.

[0072] As the N-vinyl cyclic amide represented by formula (B), N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidone, N-vinyl-2-caprolactam, N-vinyl-3-morpholinone, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, etc. are preferred, more preferably N-vinyl-2-pyrrolidone, N-vinyl-2-caprolactam, and even more preferably N-vinyl-2-pyrrolidone.

[0073] Examples of (meth)acrylamides include (meth)acrylamide, N-alkyl(meth)acrylamide, N,N-dialkyl(meth)acrylamide, etc. Examples of N-alkyl(meth)acrylamide include N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nn-butyl(meth)acrylamide, N-octylacrylamide, etc. Examples of N-alkyl(meth)acrylamides include (meth)acrylamides having an amino group, such as dimethylaminoethyl(meth)acrylamide, diethylaminoethyl(meth)acrylamide, and dimethylaminopropyl(meth)acrylamide.

[0074] Examples of N,N-dialkyl(meth)acrylamides include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(t-butyl)(meth)acrylamide.

[0075] (Meth)acrylamides also include, for example, various N-hydroxyalkyl (meth)acrylamides. Examples of N-hydroxyalkyl (meth)acrylamides include N-methylol (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, N-(4-hydroxybutyl) (meth)acrylamide, and N-methyl-N-2-hydroxyethyl (meth)acrylamide.

[0076] (Meth)acrylamides also include, for example, various N-alkoxyalkyl(meth)acrylamides, such as N-methoxymethyl(meth)acrylamide and N-butoxymethyl(meth)acrylamide.

[0077] Examples of nitrogen atom-containing monomers other than N-vinyl cyclic amides and (meth)acrylamides include amino group-containing monomers such as aminoethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, dimethylaminopropyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinyloxazole, vinylisoxazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, N-methyl Examples of the monomer include heterocyclic ring-containing monomers such as vinylpyrrolidone; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-laurylitaconimide, and N-cyclohexylitaconimide; and succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide; and other imide group-containing monomers; and isocyanate group-containing monomers such as 2-(meth)acryloyloxyethylisocyanate.

[0078] The content of the nitrogen atom-containing monomer in the monomer group is, for example, 40% by weight or less, and may be 35% by weight or less, 30% by weight or less, 25% by weight or less, 20% by weight or less, 15% by weight or less, 10% by weight or less, or even 8% by weight or less. The lower limit of the content may be, for example, 1% by weight or more, 3% by weight or more, or even 5% by weight or more. The monomer group may not contain a nitrogen atom-containing monomer.

[0079] The monomer group preferably contains a carboxyl group-containing monomer and / or a nitrogen atom-containing monomer, and more preferably contains both a carboxyl group-containing monomer and a nitrogen atom-containing monomer. In particular, when a nitrogen atom-containing monomer, particularly both a nitrogen atom-containing monomer and a carboxyl group-containing monomer, is present in the photopolymerization system, the molecular weight of the polymer tends to increase. This tendency may be due to the fact that the viscosity of the polymerization system increases due to the formation of hydrogen bonds, which suppresses the termination reaction between the growing ends of the polymer, making it easier for the monomer to remain at the end of the growing chain. The molecular weight of the polymer may affect the amount of creep of the pressure-sensitive adhesive sheet 1.

[0080] In the pressure-sensitive adhesive composition, each of the above-mentioned monomers may be contained as a polymer. When the pressure-sensitive adhesive composition is photocurable, the polymer is preferably a partial polymer. The partial polymer may be either a homopolymer or a copolymer. The partial polymer can contribute to the stable formation of a coating layer described later by appropriately increasing the viscosity of the pressure-sensitive adhesive composition.

[0081] The pressure-sensitive adhesive composition may contain a photopolymerization initiator. An example of the photopolymerization initiator is a photoradical generator that generates radicals by irradiation with light. The photopolymerization initiator may have an absorption coefficient for light of 340 nm, for example, of 0.1 L / (g·cm) or more, 0.5 L / (g·cm) or more, 1.0 L / (g·cm) or more, 3.0 L / (g·cm) or more, or even 5.0 L / (g·cm) or more. The upper limit of this absorption coefficient is not particularly limited, and is, for example, 50 L / (g·cm) or less. The absorption coefficient of the photopolymerization initiator is a calculated value from the absorbance of a 0.01 mg / mL methanol solution measured by a visible-ultraviolet spectrophotometer using a quartz cell with a path length of 1 cm.

[0082] Examples of photopolymerization initiators include benzoin ethers such as benzoin methyl ether, benzoin isopropyl ether, and benzil dimethyl ketal; substituted benzoin ethers such as anisole methyl ether; substituted acetophenones such as 2,2-diethoxyacetophenone and 2,2-dimethoxy-2-phenylacetophenone; α-hydroxyalkylphenones such as 1-hydroxycyclohexyl-phenyl ketone, 2-hydroxy-2-methylpropiophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, and 2,2'-dihydroxy-2,2'-dimethyl-1,1'-[methylenebis(4,1-phenylene)]bis(propan-1-one); and substituted alpha alkyl phenones such as 2-methyl-2-hydroxypropiophenone. -ketols; aromatic sulfonyl chlorides such as 2-naphthalenesulfonyl chloride; photoactive oximes such as 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime; benzophenone compounds such as benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, and 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone; thioxanthone compounds such as thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and 2,4-diethylthioxanthone;2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, 2-piperonyl-4,6-bis(trichloromethyl)-s-triazine, 2,4-bis(trichloromethyl)-6-styryl-s-triazine, 2-(naphth-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxy-naphth-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2,4-trichloromethyl-(piperonyl)-6-triazine, 2,4-trichloromethyl- triazine-based compounds such as (4'-methoxystyryl)-6-triazine; oxime ester-based compounds such as 1,2-octanedione, 1-[4-(phenylthio)-, 2-(O-benzoyloxime)], O-(acetyl)-N-(1-phenyl-2-oxo-2-(4'-methoxy-naphthyl)ethylidene)hydroxylamine; phosphine-based compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide; quinone-based compounds such as 9,10-phenanthrenequinone, camphorquinone, and ethylanthraquinone; borate-based compounds; carbazole-based compounds; imidazole-based compounds; and titanocene-based compounds. The adhesive composition may contain one or more photopolymerization initiators. In addition, α-hydroxyalkylphenones tend to have high absorption of light with a wavelength of 340±10 nm.;

[0083] Another example of the photopolymerization initiator is a compound having a chemical structure shown in the following formula (1) (hereinafter, referred to as chemical structure X) in the molecule. [ka]

[0084] R in the above formula (1) 1 and R 2 are each independently a C1 to C8 alkyl group; -OH, a C1 to C4 alkoxy group, -CN, -COOR51 , -OOCR 52 , or -NR 53 R 54 an alkyl group having 1 to 4 carbon atoms, the hydrogen atom of which is replaced by -CH2-C6H4-R; an alkenyl group having 3 to 6 carbon atoms, the hydrogen atom of which is replaced by -CH2-C6H4-R 55 R 1 and R 2 may be bonded to each other to form a C2 to C9 alkylene group, a C3 to C6 oxyalkylene group, or an azaalkylene group. 51 is a C1 to C8 alkyl group. 52 is a C1 to C4 alkyl group. 53 and R 54 are each independently a hydrogen atom, a C1-C12 alkyl group; -OH, a C1-C4 alkoxy group, -CN and -COOR 59 R is a C2-C4 alkyl group, the hydrogen atom of which is substituted with at least one group selected from the group consisting of: a C3-C5 alkenyl group; or a cyclohexyl group. 53 and R 54 are bonded to each other to form -O- or -N(R 60 R may be a C3 to C9 alkylene group optionally interrupted by -. 55 is a C1 to C4 alkyl group. 59 is a C1 to C4 alkyl group. 60 is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, an allyl group, a hydroxyalkyl group having 1 to 4 carbon atoms, -CH2CH2-COOR 61 Or -CH2CH2CN. 61 is a C1 to C4 alkyl group.

[0085] X is -OR 56 , or -NR 57 R 58 R 56 is a hydrogen atom, -SiR 62 3. A C1 to C8 alkyl group or a C3 to C6 alkenyl group. R 57 and R 58 represents an alkyl group having 1 to 12 carbon atoms; -OH, an alkoxy group having 1 to 4 carbon atoms, -CN and -COOR63 R is a C2-C4 alkyl group, the hydrogen atom of which is substituted with at least one group selected from the group consisting of: a C3-C5 alkenyl group; or a cyclohexyl group. 57 and R 58 are bonded to each other to form -O- or -N(R 64 R may be a C3 to C9 alkylene group optionally interrupted by -. 62 is a C1 to C6 alkyl group. 63 is a C1 to C4 alkyl group. 64 is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, an allyl group, a hydroxyalkyl group having 1 to 4 carbon atoms, -CH2CH2-COOR 65 Or -CH2CH2CN. 65 is a C1 to C4 alkyl group.

[0086] The chemical structure X can be bonded to a hydrogen atom or a structure substituted with a hydrogen atom via the carbon atom indicated by * in formula (1).

[0087] The alkyl group, alkoxy group, alkenyl group, alkylene group, oxyalkylene group, azaalkylene group, and hydroxyalkyl group described in the explanation of formula (1) may be unbranched or branched. In addition, the description of "Cn1 to Cn2" (n1 and n2 are natural numbers) in this specification, including the explanation of formula (1), means that the number of carbon atoms is in the range of n1 to n2.

[0088] R 1 and R 2 may be, independently of each other, a C1 to C8 alkyl group, a C3 to C6 alkenyl group, or a C1 to C8 alkyl group. 1 and R 2 may be, independently of each other, a C1 to C4 alkyl group, a C1 to C3 alkyl group, or a C1 to C2 alkyl group. 1 and R 2 may be a methyl group.

[0089] R 1and R 2 may be identical.

[0090] X is -OR 56 R 56 may be a hydrogen atom or a C1 to C8 alkyl group, or may be a hydrogen atom In other words, X may be -OH.

[0091] R 1 , R 2 and X may be any combination of the preferred examples above.

[0092] The chemical structure X may be a structure shown in the following formula (2). In the chemical structure X of formula (2), when a hydrogen atom substitution structure is bonded to the carbon atom indicated by *, the substitution structure and -COCR in formula (2) may be bonded to each other. 1 XR 2 The group is in a para-position relationship with respect to the benzene ring of the chemical structure X. [ka]

[0093] The photopolymerization initiator may be a compound having two or more chemical structures X in one molecule.

[0094] The photopolymerization initiator may be a compound represented by the following formula (3). The compound of formula (3) has two chemical structures X in one molecule. The two chemical structures X are located at both ends of the molecule of the photopolymerization initiator, respectively. More specifically, the two chemical structures X are bonded to each other by -A- at the carbon atom of the phenylene group represented by * above. [ka]

[0095] R in Equation (3) 1 ' and R 2 ' are each other and R 1 and R 2 Independently of R 1 and R2 R is a possible group. 1 ' and / or R 2 ' is R 1 and / or R 2 It may be the same as R 1 , R 2 , R 1 ' and R 2 ' may all be the same.

[0096] X' in formula (3) is a possible group for X, independent of X in formula (1). X' and X may be the same.

[0097] A is -O-, -CYR 3 - or -C(CH3)R 4 It is.

[0098] Y is a hydrogen atom, -Cl, -Br, -OR 71 , -NR 72 R 73 , or -SR 74 R 3 is a hydrogen atom, an alkyl group having C1 to C8, an alkenyl group having C3 to C6, a benzyl group, -CH2-C6H4-R 75 or a phenyl group. 4 is a C1 to C6 alkyl or alkylene group, and this alkylene group is bonded to a carbon atom of the phenylene group that the compound of formula (3) has.

[0099] R 71 is a hydrogen atom, -Si(R 76 )3, C1-C12 alkyl groups, C2-C18 acyl groups, -CO-NH-R 77 , C2-C20 hydroxyalkyl group, C2-C20 methoxyalkyl group, 3-R 78 -2-hydroxypropyl group, 3-[1,3,3,3-tetramethyl-1-[(trimethylsilyl)oxy]disiloxanyl]propyl group, 2,3-dihydroxypropyl group, or a C2-C21 hydroxyalkyl group or a C3-C25 alkyl group in which the carbon chain is interrupted by 1 to 9 oxygen atoms. 72and R 73 are each independently a C1 to C12 alkyl group; -OH, a C1 to C4 alkoxy group, -CN, or -COOR 79 R is a C2-C4 alkyl group in which a hydrogen atom is substituted with at least one group selected from the group consisting of: a C3-C5 alkenyl group; a cyclohexyl group; or a C7-C9 phenylalkyl group. 72 and R 73 are bonded to each other to form -O- or -N(R 80 R may be a C3 to C9 alkylene group optionally interrupted by -. 74 is an alkyl group having C1 to C18, a hydroxyethyl group, a 2,3-dihydroxypropyl group, a cyclohexyl group, a benzyl group, a phenyl group, an alkylphenyl group having C1 to C12, -CH2-COOR 81 -CH2CH2-COOR 82 or -CH(CH3)-COOR 83 R 75 is a C1 to C4 alkyl group. 76 is a C1 to C6 alkyl group. 77 is a C1 to C12 alkyl group. 78 is a C1 to C18 alkoxy group. 79 is a C1 to C4 alkyl group. 80 is a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, an allyl group, a benzyl group, a hydroxyalkyl group having 1 to 4 carbon atoms, -CH2CH2-COOR 84 , or -CH2CH2CN. 81 , R 82 and R 83 are each independently a C1 to C18 alkyl group. 84 is a C1 to C4 alkyl group.

[0100] The alkyl group, alkenyl group, acyl group, hydroxyalkyl group, methoxyalkyl group, alkoxy group, alkyl moiety in the phenylalkyl group, and alkylene group described in the explanation of formula (3) may be either unbranched or branched.

[0101] R in Equation (3) 1 , R 2 , R 1 ' and R 2 Preferred examples of R 1 and R 2 The preferred examples of X' in formula (3) are the same as the preferred examples of X described above in the explanation of formula (1). A is -CYR 3 Y may be a hydrogen atom. 3 may be a hydrogen atom. 3 - and Y and R 3 and may both be hydrogen atoms. In other words, A may be -CH2-.

[0102] R in Equation (3) 1 , R 2 , R 1 ', R 2 X′, X′, and A may take any combination of the preferred examples above.

[0103] The photopolymerization initiator may be a compound represented by the following formula (4): The compound of formula (4) is a type of compound of formula (3). [ka]

[0104] Specific examples of the photopolymerization initiator are shown in the following formulas (5) to (9). The photopolymerization initiator may be a compound represented by at least one formula selected from the group consisting of formulas (5) to (9), a compound represented by at least one formula selected from the group consisting of formulas (5) to (8), a compound represented by at least one formula selected from the group consisting of formulas (5) to (7), or a compound represented by formula (5). The compound represented by formula (8) is derived from a vinyl compound having a chemical structure X in its side chain. More specifically, it is an oligomer of the vinyl compound.

[0105] [ka]

[0106] [ka]

[0107] [ka]

[0108] [ka]

[0109] [ka]

[0110] The photopolymerization initiators represented by the formulas (5) to (9) are commercially available as Omnirad127, Esacure KIP160, Esacure one, Esacure KIP150, and Omnirad1173 (all manufactured by IGM Resins). The photopolymerization initiator may be at least one selected from these groups.

[0111] Specific examples of photoinitiators include 1-hydroxycyclohexyl-phenyl ketone, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)2-methylpropan-1-one, and 2,2-dimethoxy-2-phenylacetophenone. Each of the above photoinitiators is commercially available as Omnirad 184, Omnirad 819, Omnirad 127, and Omnirad 651 (all manufactured by IGM Resin).

[0112] The amount of the photopolymerization initiator in the pressure-sensitive adhesive composition is, for example, 20 parts by weight or less, and may be 10 parts by weight or less, 5.0 parts by weight or less, 3.0 parts by weight or less, 1.0 parts by weight or less, 0.5 parts by weight or less, 0.3 parts by weight or less, 0.25 parts by weight or less, 0.2 parts by weight or less, 0.15 parts by weight or less, 0.1 parts by weight or less, or even 0.05 parts by weight or less, based on 100 parts by weight of the total of the monomer group and its polymer. The lower limit of the amount is, for example, 0.01 parts by weight or more, and may be 0.03 parts by weight or more, based on 100 parts by weight of the total of the monomer group and its polymer.

[0113] The pressure-sensitive adhesive composition may contain a crosslinking agent. An example of the crosslinking agent is a polyfunctional monomer having two or more polymerizable functional groups in one molecule. The polyfunctional monomer may be a (meth)acrylic monomer. An example of the polyfunctional monomer is a monomer having two or more C=C bonds in one molecule, and a monomer having one or more C=C bonds and one or more polymerizable functional groups such as epoxy groups, aziridine groups, oxazoline groups, hydrazine groups, methylol groups, etc. in one molecule. The polyfunctional monomer is preferably a monomer having two or more C=C bonds in one molecule.

[0114] Examples of the polyfunctional monomer include (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, 1,2-ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol diacrylate (N DDA), 1,12-dodecanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, and other polyfunctional acrylates (such as ester compounds of polyhydric alcohols and (meth)acrylic acid); allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, epoxy acrylate, polyester acrylate, urethane acrylate, butyl di(meth)acrylate, and hexyl di(meth)acrylate. The polyfunctional monomer is preferably a polyfunctional acrylate, and more preferably 1,9-nonanediol diacrylate, trimethylolpropane tri(meth)acrylate, hexanediol di(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0115] The crosslinking agent may contain a crosslinking agent other than the above-mentioned polyfunctional monomer. Examples of the other crosslinking agent include an isocyanate-based crosslinking agent. The pressure-sensitive adhesive composition may contain an isocyanate-based crosslinking agent as a crosslinking agent, or may contain both the above-mentioned polyfunctional monomer and an isocyanate-based crosslinking agent. The isocyanate-based crosslinking agent may contribute to improving the anchoring force between the pressure-sensitive adhesive sheet 1 and the optical film.

[0116] As the isocyanate-based crosslinking agent, a compound having at least two isocyanate groups (isocyanate compound) can be used. The number of isocyanate groups contained in the isocyanate compound is preferably 3 or more. The upper limit of the number of isocyanate groups is not particularly limited, and is, for example, 5. Examples of the isocyanate compound include an aromatic isocyanate compound, an alicyclic isocyanate compound, and an aliphatic isocyanate compound.

[0117] Examples of aromatic isocyanate compounds include phenylene diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 4,4'-toluidine diisocyanate, 4,4'-diphenylether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate, and xylylene diisocyanate.

[0118] Examples of alicyclic isocyanate compounds include 1,3-cyclopentene diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, and hydrogenated tetramethylxylylene diisocyanate.

[0119] Examples of the aliphatic isocyanate compound include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (HDI), pentamethylene diisocyanate (PDI), 1,2-propylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0120] Examples of the isocyanate-based crosslinking agent include polymers (dimers, trimers, pentamers, etc.) of the above-mentioned isocyanate compounds, adducts obtained by adding them to polyhydric alcohols such as trimethylolpropane, urea-modified products, biuret-modified products, allophanate-modified products, isocyanurate-modified products, carbodiimide-modified products, and urethane prepolymers obtained by adding them to polyether polyols, polyester polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, and the like.

[0121] The isocyanate-based crosslinking agent preferably includes an aliphatic isocyanate compound and / or a derivative of an aliphatic isocyanate compound. The isocyanate-based crosslinking agent is particularly preferably at least one selected from the group consisting of pentamethylene diisocyanate (PDI)-based crosslinking agents (PDI and its derivatives) and hexamethylene diisocyanate (HDI)-based crosslinking agents (HDI and its derivatives). Specific examples of PDI-based crosslinking agents include isocyanurate-modified PDI. Specific examples of HDI-based crosslinking agents include isocyanurate-modified HDI and biuret-modified HDI.

[0122] The amount of the crosslinking agent in the pressure-sensitive adhesive composition varies depending on the molecular weight, the number of functional groups, etc., but may be, for example, 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or even 0.5 parts by weight or less, relative to 100 parts by weight of the total of the monomer group and its polymer. The smaller the amount of the crosslinking agent in the pressure-sensitive adhesive composition, the greater the amount of creep of the pressure-sensitive adhesive sheet 1 tends to be. The lower limit of the amount may be, for example, 0.01 parts by weight or more, 0.05 parts by weight or more, or even 0.1 parts by weight or more.

[0123] When the pressure-sensitive adhesive composition contains an isocyanate-based crosslinking agent, the amount of the isocyanate-based crosslinking agent may be, for example, 0.02 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, 0.5 parts by weight or more, or even 1 part by weight or more, relative to 100 parts by weight of the total of the monomer group and its polymer. When the pressure-sensitive adhesive composition contains an isocyanate-based crosslinking agent, adjusting the amount of the hydroxyl group-containing monomer in the pressure-sensitive adhesive composition to a small value tends to further improve the anchoring force between the pressure-sensitive adhesive sheet 1 and the optical film.

[0124] When an isocyanate-based crosslinking agent is added, the pressure-sensitive adhesive sheet may become hard, especially in a high-temperature environment. In such a case, the stress relaxation property of the pressure-sensitive adhesive sheet is impaired, so that the expansion and contraction stress of the optical film is easily transmitted to the interface between the pressure-sensitive adhesive sheet and the adherend, and peeling tends to occur. When the anchoring force between the pressure-sensitive adhesive sheet and the optical film can be secured by a means other than the addition of an isocyanate-based crosslinking agent, it is preferable that the pressure-sensitive adhesive composition does not contain an isocyanate-based crosslinking agent.

[0125] The pressure-sensitive adhesive composition may further contain a rework improver. The rework improver is a component that segregates on the surface of an adherend when the pressure-sensitive adhesive sheet 1 is attached to an adherend such as alkali-free glass or a transparent conductive layer, thereby reducing the adhesive strength (for example, adhesive strength P0 described below) between the pressure-sensitive adhesive sheet 1 and the adherend.

[0126] The rework improver may be, for example, a silane coupling agent having an alkoxysilyl group, and preferably further has a polar group together with the alkoxysilyl group. In the rework improver, specific examples of the alkoxy group contained in the alkoxysilyl group include a methoxy group and an ethoxy group. Examples of the polar group include a carboxyl group, an acid anhydride group, and an epoxy group. The carboxyl group may be a group generated by hydrolysis of an acid anhydride group. Examples of the acid anhydride group include a carboxylic anhydride group such as a succinic anhydride group, a phthalic anhydride group, and a maleic anhydride group. The rework improver may have an ether group other than an epoxy group, or may have a polyether skeleton.

[0127] The rework improver preferably has at least one selected from the group consisting of an acid anhydride group and an epoxy group. When a rework improver having an acid anhydride group or an epoxy group is used, the adhesive strength between the adhesive sheet 1 and the glass (adhesive strength P1 described later) tends to be improved by attaching the adhesive sheet 1 to non-alkali glass and then performing a heat treatment.

[0128] Examples of the rework improver include an alkoxysilane compound having a polar group, an organopolysiloxane compound having a polar group and an alkoxysilyl group, and a polyether compound having an alkoxysilyl group.

[0129] Examples of alkoxysilane compounds having a polar group include 2-trimethoxysilylethylsuccinic anhydride, 3-trimethoxysilylpropylsuccinic anhydride (manufactured by Shin-Etsu Chemical Co., Ltd., product name "X-12-967C"), 3-triethoxysilylpropylsuccinic anhydride, 3-methyldiethoxysilylpropylsuccinic anhydride, and 1-carboxy-3-triethoxysilylpropylsuccinic anhydride.

[0130] Examples of organopolysiloxane compounds having a polar group and an alkoxysilyl group include an acid anhydride group-containing oligomer-type silane coupling agent (product name "X-24-9591F") manufactured by Shin-Etsu Chemical Co., Ltd., and an epoxy group-containing oligomer-type silane coupling agent (product names "X-41-1053", "X-41-1059A", "X-41-1056", "X-40-2651", etc.).

[0131] Examples of polyether compounds having an alkoxysilyl group include MS Polymer S203, S303, S810, SILYL EST250, EST280, SAT10, SAT200, SAT220, SAT350, and SAT400 manufactured by Kaneka Corporation, and EXCESTAR S2410, S2420, and S3430 manufactured by Asahi Glass Co., Ltd.

[0132] The amount of the rework improver in the pressure-sensitive adhesive composition is, for example, 0.01 parts by weight or more, and may be 0.05 parts by weight or more, 0.1 parts by weight or more, 0.2 parts by weight or more, 0.5 parts by weight or more, or even 0.6 parts by weight or more, based on 100 parts by weight of the total of the monomer group and its polymer. The upper limit of the amount is, for example, 10 parts by weight or less, 5 parts by weight or less, or even 1 part by weight or less. The pressure-sensitive adhesive composition may not contain a rework improver.

[0133] The pressure-sensitive adhesive composition may contain additives other than those described above. Examples of the additives include a chain transfer agent, a silane coupling agent other than a rework improver, a viscosity modifier, a tackifier, a plasticizer, a softener, an antiaging agent, a filler, a colorant, an antioxidant, a surfactant, an antistatic agent, and an ultraviolet absorbing agent.

[0134] The content of the solvent in the pressure-sensitive adhesive composition is, for example, 5% by weight or less, and may be 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, or even 0.5% by weight or less. The pressure-sensitive adhesive composition may be substantially free of a solvent. The phrase "substantially free of a solvent" means that the solvent derived from additives or the like is allowed to be present at a content of, for example, 0.1% by weight or less, preferably 0.05% by weight or less, more preferably 0.01% by weight or less.

[0135] The viscosity of the pressure-sensitive adhesive composition is preferably 5 to 150 poise. A pressure-sensitive adhesive composition having a viscosity in the above range is particularly suitable for forming a coating layer, which will be described later.

[0136] (Physical properties of adhesive sheet) The polymerization rate of the monomer group in the pressure-sensitive adhesive sheet 1 is preferably 90% or more. The polymerization rate may be 95% or more, 98% or more, or even 99% or more.

[0137] The gel fraction of the pressure-sensitive adhesive sheet 1 is, for example, 50% or more, and may be 75% or more, 80% or more, or even 85% or more.

[0138] (Method of manufacturing pressure-sensitive adhesive sheet) The method for producing the adhesive sheet 1 is not particularly limited. As an example, when the adhesive composition is photocurable, the adhesive sheet 1 can be produced by the following method. First, as shown in FIG. 5A and FIG. 5B, a first laminate 15 is produced, which includes a base sheet 21, a coating layer 22 containing an adhesive composition, and a release liner 23 in this order. A cured sheet 20 is formed from the coating layer 22 by irradiating the first laminate 15 with light 14 (FIG. 5C). The release liner 23 is peeled off from the cured sheet 20, and a surface modification treatment is performed on the exposed surface of the cured sheet 20. The surface modification treatment is performed, for example, by irradiating the exposed surface of the cured sheet 20 with active energy rays 13 (FIG. 5D). The adhesive sheet 1 is formed from the cured sheet 20 by the surface modification treatment (FIG. 5E). In detail, a second layer 6 having a high elastic modulus is formed in the portion that has been subjected to the surface modification treatment, and a first layer 5 is formed as the remaining portion.

[0139] Irradiation of the first laminate 15 with light 14 is typically performed from the side of the base sheet 21 (FIG. 5A). At this time, the light 14 penetrates the base sheet 21 to reach the coating layer 22 and cure the coating layer 22. However, irradiation with light 14 may be performed from the side of the release liner 23, or from both the side of the release liner 23 and the base sheet 21 (FIG. 5B). The cured sheet 20 formed from the coating layer 22 is sandwiched between the base sheet 21 and the release liner 23 until the release liner 23 is peeled off, and constitutes a part of the second laminate 16.

[0140] The light 14 is, for example, visible light or ultraviolet light having a wavelength shorter than 450 nm. The light 14 may contain light having a wavelength in the same region as the absorption wavelength of the photopolymerization initiator contained in the pressure-sensitive adhesive composition. Light with a wavelength of 300 nm or less cut by a filter or the like may be irradiated, and cutting short wavelength light is suitable for suppressing deterioration of the base sheet 21 and / or the release liner 23 caused by the light 14. The light source of the light 14 is, for example, a light irradiation device equipped with an ultraviolet irradiation lamp. Examples of the ultraviolet irradiation lamp include a light-emitting diode (LED), a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an extra-high-pressure mercury lamp, a metal halide lamp, a xenon lamp, a microwave-excited mercury lamp, a black light lamp, a chemical lamp, a germicidal lamp, a low-pressure discharge mercury lamp, and an excimer laser. Two or more ultraviolet irradiation lamps may be combined. With an LED, the band of the irradiated ultraviolet light can be narrowed compared to the case of using other light sources.

[0141] The light source of the light 14 may be an LED that irradiates light with a peak wavelength of 300 to 450 nm, or an LED that irradiates light with a peak wavelength of 340±10 nm (hereinafter referred to as LED 340). According to the study by the present inventors, the use of LED 340 may contribute to at least one of the following selected from the improvement of the polymerization rate of the monomer group in the adhesive sheet 1 (specifically, the cured sheet 20), the improvement of the molecular weight of the polymer, and the reduction of the remaining amount of the photopolymerization initiator, compared to the use of a black light source, for example. In addition, the LED 340 tends to suppress heat generation compared to the use of an LED that emits light with a peak wavelength of about 365 nm. The suppression of heat generation can contribute to the control of the temperature of the coating layer 22. The peak wavelength means the wavelength at which the intensity is at a maximum value in a spectrum showing the relationship between the wavelength and intensity of light.

[0142] The illuminance of the light 14 irradiated onto the first laminate 15 (specifically, the coating layer 22) is, for example, 2.0 to 30 mW / cm 2 The illuminance is 2.5mW / cm 2 More than 3.0mW / cm 2 More than 3.5mW / cm 2More than 4.0mW / cm 2 More than 5.0mW / cm 2 More than 6.0mW / cm 2 More than 7.0mW / cm 2 More than 8.0mW / cm 2 More than 9.0mW / cm 2 or more, even 10mW / cm 2 The upper limit of the illuminance is, for example, 25 mW / cm 2 Less than 20mW / cm 2 Below 15mW / cm 2 It may be the following.

[0143] The time for irradiating the first laminate 15 (specifically, the coating layer 22) with the light 14 is, for example, 10 seconds to 1000 seconds, and may be 60 seconds or more, 100 seconds or more, 150 seconds or more, 200 seconds or more, 250 seconds or more, or even 300 seconds or more. The upper limit of the time is, for example, 800 seconds or less, and may be 600 seconds or less, 500 seconds or less, 400 seconds or less, 350 seconds or less, 300 seconds or less, or even 250 seconds or less. The irradiation with the light 14 may be continuous or intermittent.

[0144] The integrated amount of light 14 on the first laminate 15 (specifically, the coating layer 22) is, for example, 25 mJ / cm 2 More than 100 mJ / cm 2 More than 250mJ / cm 2 More than 500mJ / cm 2 More than 750mJ / cm 2 More than 850mJ / cm 2 More than 1000mJ / cm 2 More than 1250mJ / cm 2 or even 1500mJ / cm 2 The upper limit of the integrated light amount is not particularly limited, and may be, for example, 5000 mJ / cm 2 Less than 4000mJ / cm 2 Below, 3000mJ / cm 2 Below, 2500mJ / cm 2 Below, 2000mJ / cm 2 Below that, and even 1750mJ / cm 2It may be the following.

[0145] An example of the substrate of the release liner 23 (hereinafter, "liner substrate") is a resin film. Examples of resins that may be included in the liner substrate are polyesters such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyethersulfone, polycarbonate, polyamide, polyimide, polyolefin, (meth)acrylic resins, polyvinyl chloride, polyvinylidene chloride, polystyrene, polyvinyl alcohol, polyarylate, and polyphenylene sulfide. The resin is preferably a polyester such as polyethylene terephthalate.

[0146] The release liner 23 may have transparency to light 14 , or may have the same degree of transparency to light 14 as the base sheet 21 .

[0147] The thickness of the release liner 23 is, for example, 10 to 200 μm, and may be 25 to 150 μm.

[0148] The release liner 23 may include a layer other than the liner substrate. The release liner 23 may include a release layer. The release liner 23 includes, for example, a liner substrate and a release layer formed on one surface of the liner substrate. This release liner 23 can be used such that the release layer is on the coating layer 22 side.

[0149] The release layer is typically a cured layer of a release agent composition containing a release agent. As the release agent, various types of release agents can be used, such as silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, fatty acid amide-based release agents, and silica powder. The release liner 23 may be provided with a cured layer of a release agent composition containing a silicone-based release agent as a main component (hereinafter, "silicone release layer"). The silicone release layer is particularly suitable for achieving both adhesion to the pressure-sensitive adhesive sheet 1 and releasability. In this specification, the main component means the component with the largest content.

[0150] The silicone-based release agent is, for example, various curable silicone materials such as addition reaction type, condensation reaction type, ultraviolet curable type, electron beam curable type, and solventless type, and an addition reaction curable silicone material is preferred. An addition reaction curable silicone material is particularly suitable for forming a release layer that has both adhesion and releasability to the pressure-sensitive adhesive sheet 1. The curable silicone material may be a silicone-modified resin in which reactive silicone is introduced into an organic resin such as urethane, epoxy, or alkyd resin by graft polymerization or the like.

[0151] An example of the addition reaction curing silicone material is a polyorganosiloxane having a vinyl group or an alkenyl group in the molecule. The addition reaction curing silicone material may not have a hydrosilyl group. Examples of the alkenyl group are 3-butenyl, 4-pentenyl, 5-hexenyl, 6-heptenyl, 7-octenyl, 8-nonenyl, 9-decenyl, 10-undecenyl, and 11-dodecenyl. Examples of the polyorganosiloxane are polyalkylalkylsiloxanes such as polydimethylsiloxane, polydiethylsiloxane, and polymethylethylsiloxane, polyalkylarylsiloxane, and copolymers of multiple types of Si atom-containing monomers such as poly(dimethylsiloxane-diethylsiloxane). The polyorganosiloxane is preferably polydimethylsiloxane.

[0152] A release agent composition containing a silicone-based release agent as a main component (hereinafter referred to as "silicone release agent composition") usually contains a crosslinking agent. An example of the crosslinking agent is polyorganosiloxane having a hydrosilyl group. The crosslinking agent may have two or more hydrosilyl groups in one molecule.

[0153] The silicone release agent composition may contain a curing catalyst. An example of the curing catalyst is a platinum catalyst. An example of the platinum catalyst is chloroplatinic acid, an olefin complex of platinum, or an olefin complex of chloroplatinic acid. The amount of the platinum catalyst used is, for example, 10 to 1000 ppm (weight basis, platinum equivalent) based on the total solid content of the composition.

[0154] The silicone release agent composition may contain additives. Examples of additives are release control agents and adhesion promoters. Examples of release control agents are unreactive silicone resins, and more specific examples are organosiloxanes such as octamethylcyclotetrasiloxane, and MQ resins. The amount of the release control agent and adhesion promoter used is, for example, 1 to 30% by weight in total based on the total solid content of the composition. Further examples of additives are fillers, antistatic agents, antioxidants, ultraviolet absorbers, plasticizers, and colorants. The amount of the further additives used is, for example, 10% by weight or less in total based on the total solid content of the composition.

[0155] The silicone release agent composition may contain an organic solvent. Examples of the organic solvent include hydrocarbon solvents such as cyclohexane, n-hexane, and n-heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, and butanol. Two or more organic solvents may be contained. The amount of the organic solvent used is preferably 80 to 99.9% by weight of the silicone release agent composition.

[0156] The release layer can be formed, for example, by heating and drying a coating film containing the release agent composition formed on a liner substrate. Various coating methods such as roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating can be applied to apply the release agent composition. For example, hot air drying can be applied to apply the heating and drying. The heating temperature and time vary depending on the heat resistance of the liner substrate, but are usually about 80 to 150°C and 10 seconds to 10 minutes. If necessary, irradiation with active energy rays such as ultraviolet rays may be used in combination.

[0157] The thickness of the release layer is, for example, 10 to 300 nm. The upper limit of the thickness may be 200 nm or less, 150 nm or less, 120 nm or less, 110 nm or less, 100 nm or less, less than 100 nm, 90 nm or less, 80 nm or less, 70 nm or less, less than 70 nm, or even 65 nm or less. The lower limit of the thickness may be 15 nm or more, 20 nm or more, 25 nm or more, 30 nm or more, 35 nm or more, 40 nm or more, 45 nm or more, or even 50 nm or more.

[0158] The release liner 23 may be in the form of a sheet or a continuous piece.

[0159] An example of the base sheet 21 is a resin film. Examples of the resin contained in the base sheet 21 are the same as the examples of the resin that can be contained in the liner base material.

[0160] The base sheet 21 preferably has excellent light 14 transmittance.

[0161] The thickness of the base sheet 21 is, for example, 10 to 200 μm, and may be 25 to 150 μm.

[0162] The base sheet 21 may have a release layer on the surface on the side of the coating layer 22. Examples of the release layer that the base sheet 21 may have and the manufacturing method thereof are the same as the examples of the release layer that the release liner 23 may have and the manufacturing method thereof. Both the release liner 23 and the base sheet 21 may have a release layer. In this case, both release layers may be formed from a release agent composition containing the same release agent as a main component. In addition, the thicknesses of both release layers may be different, and for example, the release layer provided on the base sheet 21 may be thicker.

[0163] For the base sheet 21 , a sheet having a greater peel strength from the cured sheet 20 than the release liner 23 can usually be selected.

[0164] The base sheet 21 may be in the form of a sheet or a long piece.

[0165] The first laminate 15 can be formed, for example, by forming a coating layer 22 on a base sheet 21 (or a release liner 23) and then disposing a release liner 23 (or a base sheet 21) on the formed coating layer 22. Alternatively, the first laminate 15 may be formed by applying a pressure-sensitive adhesive composition in a poured manner into the space between the base sheet 21 and the release liner 23 that are held at a predetermined distance such that their main surfaces face each other.

[0166] The coating layer 22 can be formed by various coating methods such as roll coating, kiss roll coating, gravure coating, reverse coating, roll brush, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating.

[0167] The thickness of coating layer 22 can be adjusted depending on the desired thickness of adhesive sheet 1 and may be, for example, 5 to 500 μm, 5 to 250 μm, 5 to 150 μm, 5 to 100 μm, 5 to 50 μm, 5 to 30 μm, 5 to 25 μm, or even 5 to 20 μm.

[0168] Examples of surface modification treatments performed on the cured sheet 20 include corona treatment, plasma treatment, excimer treatment, and flame treatment, with corona treatment being preferred. In other words, the active energy rays 13 may be at least one selected from the group consisting of electron beams, ion beams, plasma beams, and ultraviolet rays. Each surface modification treatment can be performed by a corresponding known treatment device. Conditions for the surface modification treatment include those described above.

[0169] [Embodiment of Optical Laminate] An example of the optical laminate of this embodiment is shown in FIG. 6. The optical laminate 10 of FIG. 6 includes the above-mentioned pressure-sensitive adhesive sheet 1 and at least one optical film 2 selected from the group consisting of a polarizing film and a retardation film. The pressure-sensitive adhesive sheet 1 is preferably in direct contact with the optical film 2. In the example of FIG. 6, the first surface 1a of the pressure-sensitive adhesive sheet 1 is in contact with the optical film 2. The optical laminate 10 may have a structure in which the base sheet used in producing the pressure-sensitive adhesive sheet 1 is laminated on the pressure-sensitive adhesive sheet 1. The optical laminate 10 can be used as an optical film with a pressure-sensitive adhesive sheet.

[0170] (Optical film) The optical film 2 has a surface 2a facing the pressure-sensitive adhesive sheet 1. For example, the surface 2a is in contact with the first surface 1a of the pressure-sensitive adhesive sheet 1. The surface 2a of the optical film 2 may be subjected to a surface modification treatment. The surface 2a subjected to the surface modification treatment tends to improve the anchoring force between the pressure-sensitive adhesive sheet 1 and the optical film 2. Examples of the surface modification treatment include those described above for the pressure-sensitive adhesive sheet 1.

[0171] The surface 2a is preferably subjected to a corona treatment as a surface modification treatment. When the surface 2a is subjected to a corona treatment, the conditions such as the discharge amount can be appropriately adjusted within the ranges described above for the pressure-sensitive adhesive sheet 1, for example.

[0172] As described above, the optical film 2 includes at least one selected from the group consisting of a polarizing film and a retardation film. The optical film 2 may be a laminated film including a polarizing film and / or a retardation film. The optical film 2 may include a glass film. However, the optical film 2 is not limited to the above examples.

[0173] The polarizing film includes a polarizer. The polarizing film typically includes a polarizer and a protective film (transparent protective film). The protective film is disposed, for example, in contact with the main surface (surface having the widest area) of the polarizer. The polarizer may be disposed between two protective films. The protective film may be disposed on at least one surface of the polarizer.

[0174] The polarizer is not particularly limited, and examples thereof include hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified ethylene-vinyl acetate copolymer films, which are uniaxially stretched after adsorbing dichroic substances such as iodine and dichroic dyes; polyene-based oriented films such as dehydrated polyvinyl alcohol and dehydrochlorinated polyvinyl chloride; etc. Polarizers are typically made of polyvinyl alcohol films (polyvinyl alcohol films include partially saponified ethylene-vinyl acetate copolymer films) and dichroic substances such as iodine.

[0175] The thickness of the polarizer is not particularly limited, and may be, for example, 80 μm or less, 50 μm or less, 30 μm or less, 25 μm or less, or even 20 μm or less. The lower limit of the thickness of the polarizer is not particularly limited, and may be, for example, 1 μm or more, 5 μm or more, 10 μm or more, or even 15 μm or more. A thin polarizer (for example, a thickness of 20 μm or less) is suppressed in dimensional change, and can contribute to improving the durability of the optical laminate, particularly the durability at high temperatures.

[0176] As the material of the protective film, for example, a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. is used. Specific examples of such thermoplastic resins include cellulose resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene-based resins), polyarylate resins, polystyrene resins, polyvinyl alcohol resins, and mixtures thereof. The material of the protective film may be a thermosetting resin or an ultraviolet-curing resin such as a (meth)acrylic, urethane, acrylic urethane, epoxy, or silicone-based resin. When the polarizing film has two protective films, the materials of the two protective films may be the same or different from each other. For example, a protective film made of a thermoplastic resin may be bonded to one main surface of the polarizer via an adhesive, and a protective film made of a thermosetting resin or an ultraviolet-curing resin may be bonded to the other main surface of the polarizer. The protective film may contain one or more types of optional additives, such as ultraviolet absorbers, antioxidants, lubricants, plasticizers, release agents, color inhibitors, flame retardants, nucleating agents, antistatic agents, pigments, and colorants.

[0177] In addition, a film containing a (meth)acrylic resin tends to have a low adhesive strength with a pressure-sensitive adhesive sheet. However, in this embodiment, the creep amount and elastic modulus G1 of the pressure-sensitive adhesive sheet 1 are appropriately adjusted, so that even when the surface of the protective film containing a (meth)acrylic resin corresponds to the surface 2a of the optical film 2, the anchoring force between the pressure-sensitive adhesive sheet 1 and the optical film 2 can be adjusted to a sufficiently high value.

[0178] The thickness of the protective film can be appropriately determined, but is generally about 10 to 200 μm in terms of strength, workability such as handleability, thinness, and the like.

[0179] The polarizer and the protective film are usually adhered to each other via a water-based adhesive or the like. Examples of the water-based adhesive include an isocyanate-based adhesive, a polyvinyl alcohol-based adhesive, a gelatin-based adhesive, a vinyl-based latex, a water-based polyurethane, and a water-based polyester. Examples of adhesives other than the above-mentioned adhesives include an ultraviolet-curable adhesive and an electron beam-curable adhesive. The electron beam-curable polarizing plate adhesive exhibits suitable adhesion to various protective films. The adhesive may contain a metal compound filler.

[0180] In the polarizing film, a retardation film or the like can be formed on the polarizer instead of the protective film. Another protective film or a retardation film or the like can be further provided on the protective film.

[0181] The protective film may have a hard coat layer on the surface opposite to the surface bonded to the polarizer, and may also be subjected to treatments for the purposes of anti-reflection, anti-sticking, diffusion, anti-glare, etc.

[0182] The polarizing film may be a circular polarizing film.

[0183] The retardation film may be one obtained by stretching a polymer film or one obtained by aligning and fixing a liquid crystal material. The retardation film has birefringence, for example, in the in-plane and / or thickness direction.

[0184] Retardation films include anti-reflection retardation films (see JP 2012-133303 A,

[0221] ,

[0222] ,

[0228] ), viewing angle compensation retardation films (see JP 2012-133303 A,

[0225] ,

[0226] ), and tilted orientation retardation films for viewing angle compensation (see JP 2012-133303 A,

[0227] ).

[0185] The specific configuration of the retardation film, for example, the retardation value, arrangement angle, three-dimensional birefringence, whether it is a single layer or a multilayer, and the like, are not particularly limited, and any known retardation film can be used.

[0186] The thickness of the retardation film is preferably 20 μm or less, more preferably 10 μm or less, further preferably 1 to 9 μm, and particularly preferably 3 to 8 μm.

[0187] The retardation film may include, for example, a quarter wave plate and / or a half wave plate in which a liquid crystal material is oriented and fixed.

[0188] (Properties of optical laminate) In this embodiment, the anchoring force F between the pressure-sensitive adhesive sheet 1 and the optical film 2 tends to be large. The anchoring force F is, for example, 10.0 N / 25 mm or more, and may be 11.0 N / 25 mm or more, 12.0 N / 25 mm or more, 13.0 N / 25 mm or more, 14.0 N / 25 mm or more, 15.0 N / 25 mm or more, 16.0 N / 25 mm or more, 17.0 N / 25 mm or more, or even 18.0 N / 25 mm or more. The upper limit of the anchoring force F is not particularly limited, and may be, for example, 50 N / 25 mm or less, or 30 N / 25 mm or less.

[0189] The anchoring force F between the adhesive sheet 1 and the optical film 2 can be measured by the following method. First, the optical laminate 10 to be evaluated is cut into a size of 25 mm wide x 150 mm long to prepare a test piece. Next, the entire surface of the optical film 2 provided on the test piece is superimposed on a stainless steel test plate via a double-sided tape, and a 2 kg roller is moved back and forth once to press them together. Next, the adhesive sheet 1 provided on the test piece is superimposed on the evaluation sheet, and a 2 kg roller is moved back and forth once to press them together. The evaluation sheet is not particularly limited as long as it has a size of 30 mm wide x 150 mm long and does not peel off from the adhesive sheet 1 during the test. For example, an ITO film (such as 125 Tetolite OES (manufactured by Oike Kogyo Co., Ltd.)) can be used as the evaluation sheet. Next, using a commercially available tensile tester, while holding the evaluation sheet, the pressure-sensitive adhesive sheet 1 is peeled off from the optical film 2 at a peel angle of 180° and a tensile speed of 300 mm / min, and the average peel force is specified as the anchoring force F between the pressure-sensitive adhesive sheet 1 and the optical film 2. The above test is performed in an atmosphere of 23°C.

[0190] From the viewpoint of reworkability, the optical laminate 10 preferably has an adhesive strength P0 determined by the following Test 1 of 8.0 N / 25 mm or less. Test 1: Adhesive sheet 1 is attached to non-alkali glass, and then peeled off from the non-alkali glass at a peel speed of 300 mm / min and a peel angle of 90°. The force required to do this (adhesive force P0) is measured.

[0191] Test 1 is performed by the following method. First, the optical laminate 10 is cut into a strip of 150 mm length × 25 mm width to prepare a test piece. Next, the test piece is attached to alkali-free glass via an adhesive sheet 1. The alkali-free glass is glass that does not substantially contain an alkali component (alkali metal oxide), and more specifically, the weight ratio of the alkali component in the glass is, for example, 1000 ppm or less, or even 500 ppm or less. The alkali-free glass is, for example, in the form of a plate, and has a thickness of 0.5 mm or more.

[0192] The test piece is attached to the alkali-free glass using, for example, a laminator, so that no air bubbles are mixed between the alkali-free glass and the adhesive sheet 1. After attaching the test piece, the test piece is placed in an autoclave at 50°C and 5 atm (absolute pressure) for 15 minutes to homogenize the bond between the alkali-free glass and the adhesive sheet 1, and the adhesive sheet 1 is adhered to the alkali-free glass. Next, the test piece is peeled off from the alkali-free glass at a peeling speed of 300 mm / min and a peeling angle of 90° (measurement length 80 mm). At this time, the force required to peel the test piece from the alkali-free glass is measured once at intervals of 0.5 s. The average value of the obtained measurements is specified as the adhesive strength P0.

[0193] The adhesive strength P0 is preferably 7.0 N / 25 mm or less, and may be 6.0 N / 25 mm or less, 5.0 N / 25 mm or less, 4.5 N / 25 mm or less, 4.0 N / 25 mm or less, or even 3.5 N / 25 mm or less. The lower limit of the adhesive strength P0 may be, for example, 0.5 N / 25 mm or more, 1.0 N / 25 mm or more, or even 1.5 N / 25 mm or more. The adhesive strength P0 is preferably 0.5 to 7.0 N / 25 mm.

[0194] The difference (F-P0) between the anchoring force F and the adhesive force P0 is preferably 5.0 N / 25 mm or more, and may be 6.0 N / 25 mm or more, 7.0 N / 25 mm or more, 8.0 N / 25 mm or more, 9.0 N / 25 mm or more, 10.0 N / 25 mm or more, 11.0 N / 25 mm or more, 12.0 N / 25 mm or more, or even 13.0 N / 25 mm or more. The upper limit of the difference (F-P0) is, for example, 20 N / 25 mm or less.

[0195] Furthermore, from the viewpoint of durability, it is preferable that the adhesiveness of the pressure-sensitive adhesive sheet 1 of the optical laminate 10 is improved when it is heat-treated in contact with alkali-free glass. As an example, it is preferable that the adhesive strength P1 of the optical laminate 10, as determined by the following test 2, is 8.0 N / 25 mm or more. Test 2: The adhesive sheet 1 is attached to non-alkali glass and heat-treated at 60°C for 100 hours. The adhesive sheet 1 is peeled off from the non-alkali glass at a peel speed of 300 mm / min and a peel angle of 90°. The force required for this (adhesive force P1) is measured.

[0196] Test 2 can be performed in the same manner as Test 1, except that the bond between the alkali-free glass and the adhesive sheet 1 is homogenized in an autoclave, then a heat treatment is performed at atmospheric pressure at 60°C for 100 hours, and the temperature of the test piece is then lowered to room temperature (e.g., 23°C) before the test piece is peeled off from the alkali-free glass.

[0197] The adhesive strength P1 is preferably 9.0 N / 25 mm or more, and may be 9.5 N / 25 mm or more, 10.0 N / 25 mm or more, or even 10.5 N / 25 mm or more. The upper limit of the adhesive strength P1 is, for example, 20 N / 25 mm or less.

[0198] Another example of the optical laminate of the present embodiment is shown in Fig. 7. The optical laminate 11 in Fig. 7 has a laminated structure in which an adhesive sheet 1, an optical film 2A, an adhesive sheet 7, and an optical film 2B are laminated in this order. The optical laminate 11 may have a structure in which the base sheet used in producing the adhesive sheet 1 is laminated on the adhesive sheet 1.

[0199] In the optical laminate 11, typically, the optical film 2A is a retardation film, and the optical film 2B is a polarizing film. The adhesive sheet 7 functions as an interlayer adhesive between the optical films 2A and 2B. The adhesive sheet 7 may be one using a known adhesive, or may be one described above for the adhesive sheet 1.

[0200] The optical laminates 10 and 11 of the present embodiment can be distributed and stored, for example, as a rolled body obtained by rolling up a strip-shaped optical laminate, or as a sheet-shaped optical laminate.

[0201] The optical laminate of this embodiment is typically used in an image display device. The image display device includes, for example, the optical laminate 10 or 11, and can be formed by bonding the optical laminate 10 or 11 to an image display panel. The bonding is performed, for example, by an adhesive sheet 1. The image display device may be an organic EL display or a liquid crystal display. However, the image display device is not limited to the above examples. The image display device may be an electroluminescence (EL) display, a plasma display (PD), a field emission display (FED: Field Emission Display), or the like. The image display device can be used for home appliances, in-vehicle applications, public information displays (PID), and the like. EXAMPLES

[0202] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the examples shown below.

[0203] [Monomer Syrup A1] 95.5 parts by weight of n-butyl acrylate (BA), 4.4 parts by weight of acrylic acid (AA), 0.1 parts by weight of 4-hydroxybutyl acrylate (HBA), 0.05 parts by weight of 1-hydroxycyclohexyl-phenyl ketone (Omnirad184, manufactured by IGM Resins BV) as photopolymerization initiators, and 0.05 parts by weight of 2,2-dimethoxy-2-phenylacetophenone (Omnirad651, manufactured by IGM Resins BV) were placed in a four-neck flask and irradiated with ultraviolet light under a nitrogen atmosphere to obtain a partially photopolymerized monomer syrup A1. The ultraviolet light irradiation was continued until the viscosity of the liquid in the flask (measurement conditions: BH viscometer No. 5 rotor, 10 rpm, measurement temperature 30°C) reached about 20 Pa·s.

[0204] [Monomer Syrup A2] Monomer syrup A2 was prepared in the same manner as Monomer syrup A1, except that the monomers and photopolymerization initiator were changed as shown in Table 1.

[0205] [Table 1]

[0206] The abbreviations in Table 1 are as follows. BA: n-butyl acrylate AA: Acrylic acid HBA: 4-hydroxybutyl acrylate Omnirad184: 1-Hydroxycyclohexyl-phenyl ketone (Omnirad184, IGM Resins BV) Omnirad651: 2,2-dimethoxy-2-phenylacetophenone (Omnirad651, IGM Resins BV) Omnirad819: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (Omnirad819, IGM Resins BV)

[0207] [Adhesive compositions C1 to C8] Next, the monomer syrup, the monomer, the crosslinking agent, and the silane coupling agent were mixed so as to obtain the compositions shown in Table 2 below, thereby obtaining pressure-sensitive adhesive compositions C1 to C8.

[0208] [Table 2]

[0209] The abbreviations in Table 2 are as follows. NVP: N-vinyl-2-pyrrolidone NDDA: 1,9-nonanediol diacrylate KBM403: 3-glycidoxypropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-403")

[0210] The final composition of the monomers contained in each adhesive composition is shown in Table 3 below.

[0211] [Table 3]

[0212] Example 1 [Preparation of release liner] Addition reaction curing type silicone (LTC761 containing hexenyl group-containing polyorganosiloxane, 30 wt% toluene solution, manufactured by Dow Corning Toray) 30 parts by weight, release control agent (BY24-850 containing unreactive silicone resin, manufactured by Dow Corning Toray) 0.9 parts by weight, curing catalyst (SRX212 containing platinum catalyst, manufactured by Dow Corning Toray) 2 parts by weight, and toluene / hexane mixed solvent (volume ratio 1: 1) as a dilution solvent were mixed to obtain a silicone-based release agent composition. The concentration of silicone solids in the release agent composition was 1.0 wt%. Next, the release agent composition was applied to one side of a liner substrate (Lumirror XD500P, a polyester film, thickness 75 μm) with a wire bar and heated at 130 ° C for 1 minute to prepare a release liner having a release layer (thickness 60 nm) on one side.

[0213] [Preparation of adhesive sheet] The adhesive composition C1 was applied to one side of a base sheet (PET separator, manufactured by Mitsubishi Plastics, MRF38) with an applicator to form a coating layer (thickness 20 μm). Next, a release liner was placed on the formed coating layer to obtain a first laminate. The release liner was placed so that the release layer was in contact with the coating layer. Next, light was irradiated from the side of the base sheet in the first laminate. As the light source, a combination of a black light source (BL) and an LED that irradiates light with a peak wavelength of 340 nm was used. The irradiation conditions for each light source were as follows. The illuminance of the light was measured using an illuminometer (manufactured by Topcon Technohouse, UD-T3040T2) at a position near the ultraviolet ray incident surface of the base sheet. BL: Illuminance 6.2mW / cm 2 and irradiation time 95 seconds (accumulated light intensity 589 mJ / cm 2 ) LED: Illuminance 3.1mW / cm 2 and irradiation time 90 seconds (accumulated light intensity 279 mJ / cm 2 )

[0214] The coating layer was photocured by the irradiation of light, and a second laminate was obtained that was composed of the release liner, the cured sheet (thickness 20 μm), and the base sheet. Next, the release liner was peeled off from the second laminate, and a discharge amount of 61 W / m was applied to the exposed surface of the cured sheet. 2 As a result, a layer with a high elastic modulus (second layer) was formed in the portion that had been subjected to the corona treatment, and the pressure-sensitive adhesive sheet of Example 1 was obtained.

[0215] (Examples 2 to 10 and Comparative Examples 1 to 3) Adhesive sheets of Examples 2 to 10 and Comparative Examples 1 to 3 were obtained in the same manner as in Example 1, except that the adhesive composition used and the discharge amount in the corona treatment were changed as shown in Table 4. In Comparative Example 1, no corona treatment was performed, and the cured sheet was regarded as the adhesive sheet.

[0216] [AFM measurements] - Elastic modulus of the first surface G1 and elastic modulus of the second surface G2 For the pressure-sensitive adhesive sheets of the Examples and Comparative Examples, the elastic modulus G1 of the first surface and the elastic modulus G2 of the second surface were measured using an AFM by the above-mentioned method. Note that for Examples 1 to 10 and Comparative Examples 2 and 3, the surface subjected to the corona treatment was regarded as the first surface, and for Comparative Example 1, the surface of the pressure-sensitive adhesive sheet exposed by peeling off the release liner from the second laminate was regarded as the first surface. As the scanning probe microscope, an MFP-3D stand-alone manufactured by ASYLUM RESEARCH was used.

[0217] Second layer thickness In all of the pressure-sensitive adhesive sheets of the Examples, a layer (second layer) with a high elastic modulus was formed in the area that had been subjected to the corona treatment. The thickness of this second layer was measured using an AFM by the method described above. As a result, the second layer in each of the pressure-sensitive adhesive sheets of the Examples had a thickness of about 100 nm to 150 nm. The test piece for measuring the thickness of the second layer was prepared by cutting the laminate obtained by laminating the pressure-sensitive adhesive sheet to a support film with an ultramicrotome. The support film used was a polarizing film D1 described later.

[0218] [Creep amount] The creep amount was measured for the pressure-sensitive adhesive sheets of the examples and comparative examples by the above-mentioned method. A 50 μm thick PET film was used for the support film 51. A SUS304 plate (30 mm × 75 mm, thickness 2.5 mm) was used for the test plate 53. A Keyence LK-H057 laser displacement meter was used.

[0219] [Preparation of optical laminate] Next, a polarizing film D1 was produced, and an optical laminate was produced by combining it with the pressure-sensitive adhesive sheets of the examples and comparative examples. The polarizing film D1 was prepared by the following method. First, a polyvinyl alcohol film having a thickness of 80 μm was stretched to 3 times while being dyed for 1 minute in an iodine solution having a concentration of 0.3% at a temperature of 30° C. between rolls having different speed ratios. Next, the film was stretched until the total stretch ratio became 6 times while being immersed for 0.5 minutes in an aqueous solution having a temperature of 60° C. and containing boric acid at a concentration of 4% and potassium iodide at a concentration of 10%. Next, the film was immersed for 10 seconds in an aqueous solution having a temperature of 30° C. and containing potassium iodide at a concentration of 1.5%, washed, and then dried at 50° C. for 4 minutes to obtain a polarizer having a thickness of 20 μm. A triacetyl cellulose (TAC)-based transparent protective film (thickness 25 μm, manufactured by Fujifilm Corporation) that had been subjected to a saponification treatment was attached to one side of the polarizer with a polyvinyl alcohol-based adhesive. Furthermore, a cycloolefin polymer (COP)-based transparent protective film (thickness 13 μm, manufactured by Zeon Corporation) that had been subjected to corona treatment was attached to the other surface of the polarizer using a polyvinyl alcohol-based adhesive, thereby obtaining a polarizing film D1 having a configuration of TAC-based transparent protective film / polarizer / COP-based transparent protective film.

[0220] In Examples 1 to 10 and Comparative Examples 1 to 3, the above polarizing film D1 was placed on the first surface of the pressure-sensitive adhesive sheet to produce an optical laminate. At this time, the polarizing film D1 was placed so that the surface on the COP-based transparent protective film side was in contact with the pressure-sensitive adhesive sheet.

[0221] [Anchoring power] The anchoring force F between the adhesive sheet and the polarizing film was measured by the above-mentioned method for the optical laminate produced by the above-mentioned method. The double-sided tape used was "No. 531" manufactured by Nitto Denko Corporation. The stainless steel test plate used was a SUS304 plate (width 40 mm x length 120 mm). The evaluation sheet used was an ITO film (125 Tetolite OES, manufactured by Oike Kogyo). The tensile tester used was an autograph SHIMAZU AG-I 10KN (manufactured by Shimadzu Corporation).

[0222] [Durability] The optical laminate prepared by the above method was used to evaluate durability (85°C durability) by the following method. First, the optical laminate was cut into a strip of 300mm length x 220mm width to prepare a test piece. Next, the test piece was attached to the surface of 0.7mm thick alkali-free glass (manufactured by Corning, product name "EG-XG") with an adhesive sheet. At this time, the second surface of the adhesive sheet was brought into contact with the alkali-free glass. The test piece was attached to the alkali-free glass using a laminator. After the test piece was attached, it was placed in an autoclave at 50°C and 0.5MPa for 15 minutes to homogenize the bonding between the alkali-free glass and the adhesive sheet, and the adhesive sheet was adhered to the alkali-free glass. Next, the test piece was subjected to a heat treatment at 85°C under atmospheric pressure for 500 hours. The appearance of the adhesive sheet between the polarizing film and the alkali-free glass was visually observed, and peeling and internal cracking (glue cracking) were evaluated according to the following criteria. Peeling (Evaluation Criteria) A: No peeling was observed. B: There is slight peeling at the edge, but it does not affect the image display function. C: Significant peeling that may affect image display function. · Glue cracking (Evaluation Criteria) A: No cracking of the glue was observed. B: There is a slight crack in the glue at the edge. C: There is glue tearing at the edge.

[0223] [Table 4]

[0224] As can be seen from Table 4, the adhesive sheets of the examples, in which the creep amount was 10 μm or more and the elastic modulus G1 of the first surface was 1.0 MPa or more, showed better peeling evaluation results in the durability test than the comparative examples. From this result, it is presumed that the adhesive sheets of the examples are suitable for suppressing peeling between components of an image display device in a high temperature environment. [Industrial Applicability]

[0225] The pressure-sensitive adhesive sheet of the present invention can be used, for example, in optical laminates and image display devices. [Explanation of symbols]

[0226] 1 Adhesive sheet 1a 1st surface 1b 2nd surface 2. Optical Film 5 1st layer 6 2nd layer 10,11 Optical laminate

Claims

1. A pressure-sensitive adhesive sheet having a first surface and a second surface opposed to each other, The creep amount determined by the following test is 10 μm or more, A pressure-sensitive adhesive sheet, wherein the first surface has an elastic modulus of 1.0 MPa or more as measured using an atomic force microscope. Test: The pressure-sensitive adhesive sheet is attached to a stainless steel test plate at a joint surface of 10 mm long x 10 mm wide, and a load of 500 gf is applied vertically downward with the test plate fixed. The creep amount (displacement amount) of the pressure-sensitive adhesive sheet relative to the test plate is measured 3600 seconds after the load is applied.

2. A first layer and a second layer positioned on the first layer, The adhesive sheet of claim 1 , wherein the first surface coincides with a surface of the second layer.

3. The pressure-sensitive adhesive sheet according to claim 2 , wherein the second layer has a thickness of 1.0 μm or less.

4. The pressure-sensitive adhesive sheet according to claim 1 , wherein the creep amount is 300 μm or less.

5. The pressure-sensitive adhesive sheet according to claim 1 , wherein the elastic modulus of the first surface is 10.0 MPa or less.

6. The pressure-sensitive adhesive sheet according to claim 1 , wherein the second surface has an elastic modulus of less than 1.0 MPa as measured using an atomic force microscope.

7. The pressure-sensitive adhesive sheet according to claim 1 , wherein the first surface is a surface that has been subjected to a surface modification treatment.

8. The pressure-sensitive adhesive sheet according to claim 7 , wherein the surface modification treatment is a corona treatment.

9. The pressure-sensitive adhesive sheet according to claim 1 , which is formed from a pressure-sensitive adhesive composition containing a monomer group and / or a polymer of the monomer group.

10. The pressure-sensitive adhesive sheet according to claim 9 , wherein the monomer group includes a (meth)acrylic monomer.

11. The pressure-sensitive adhesive sheet according to claim 9 , wherein the pressure-sensitive adhesive composition is photocurable.

12. The pressure-sensitive adhesive sheet according to claim 9 , wherein the pressure-sensitive adhesive composition has a solvent content of 5 wt % or less.

13. The pressure-sensitive adhesive sheet according to claim 1 , having a thickness of 50 μm or less.

14. The pressure-sensitive adhesive sheet according to any one of claims 1 to 13, An optical film including at least one selected from the group consisting of a polarizing film and a retardation film; An optical laminate comprising:

15. The optical laminate according to claim 14 , wherein the first surface of the pressure-sensitive adhesive sheet is in contact with the optical film.

16. The optical laminate according to claim 14 , wherein the anchoring strength between the pressure-sensitive adhesive sheet and the optical film is 10.0 N / 25 mm or more.

17. An image display device comprising the optical laminate according to claim 14.

Citation Information

Patent Citations

  • Optical active energy line polymerizable adhesive and optical laminate

    CN109321145A

  • Antistatic film, polarizing plate, touch panel, and liquid crystal display device

    CN110383110A

  • Method of anchoring a coating agent to a polymer surface

    DE102015221455A1

  • Re-releasable movable adhesive sheet

    JP2011132371A

  • Method for producing laminate, and laminate

    JP2014065207A